العوامل المحددة لسرعة دوران النقود في الاقتصاد الليبي دراسة قياسية: للفترة (1970-2010) - علي محمد إدريس; الدرسي محمود صالح عامر (Scientific Journal of University of Benghazi, 2021)
This study aimed to identify the determinants of the velocity of money in the Libyan economy during the period between 1970-2010. The latest quantitative measurement methods were applied to detect the stability of time series using the modified Dickey-Fuller (ADF) and Phelps Perron (PP) tests. The autoregressive approach for time gaps (ARDL) was used to reveal the existence of a cointegration relationship in the long term between the variables included in the model. The error correction model was used in the short term, as the study concluded that the most important determinants of the speed of money turnover in the Libyan economy were: (real income - the exchange rate - the number of banks - the public budget deficit - financial development - money supply) and that these variables explain ( 97%) of the changes that occur in the velocity of money in the Libyan economy. It also concluded that there is a long-term equilibrium relationship between the velocity of money and the factors determining it and that the velocity of money is directly related to real income, the exchange rate, the public budget deficit, the number of banks and the inflation rate, and in an inverse relationship with money supply and financial development in the Libyan economy. This is consistent with the stipulations of economic theory. Finally, the study recommended that the government and monetary authorities take into consideration the factors determining the velocity of money in the Libyan economy due to their importance in influencing the effectiveness of monetary policies.